IDENTIFIKASI ETNOMATEMATIKA YANG TERDAPAT DALAM PEPATAH MASYARAKAT BENGKULU “ IKAN SEJEREK, BERE SECUPAK” - Yanti, Dwi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract— The purpose of this study is to Identify the ethnomatematics contained in the proverb of the community of Bengkulu